1989
DOI: 10.1017/s0043174500072581
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tolerance of Corn Genotypes to DPX-M6316

Abstract: Ten corn inbred lines were field evaluated for their tolerance to DPX-M6316 at 32 and 64 g ai/ha. Inbreds ‘A619′, ‘A641′, and ‘ND246’ were highly susceptible to DPX-M6316; inbreds ‘A671′, ‘A632′, and ‘B73’ were highly tolerant; and inbreds ‘A654′, ‘CM105′, ‘W153R’, and ‘M017’ were intermediate in their response. The basis for differential tolerance was studied by comparing the susceptibility of acetolactate synthase (ALS) to inhibition by DPX-M6316 in tolerant A671 and susceptible A619, and by examining the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Nicosulfuron in agricultural production has been widely used as a postemergence herbicide in maize. Many studies have demonstrated that maize cultivars differ in their sensitivity to nicosulfuron (Eberline et al 1989, Wang et al 2016. Therefore, the harm that nicosulfuron causes to maize crops should be further studied in order to evaluate its impact on different corn varieties, a crucial issue in maize production that urgently needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Nicosulfuron in agricultural production has been widely used as a postemergence herbicide in maize. Many studies have demonstrated that maize cultivars differ in their sensitivity to nicosulfuron (Eberline et al 1989, Wang et al 2016. Therefore, the harm that nicosulfuron causes to maize crops should be further studied in order to evaluate its impact on different corn varieties, a crucial issue in maize production that urgently needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Safeners have been shown to enhance the activity of P450 monooxygenases (Kreuz et al, 1996). Differential sensitivity in field corn to P450-metabolized herbicides has been associated with different rates of metabolism (Bunting et al, 2004;Eberlein et al, 1989;Hinz and Owen, 1996). Previously, Bunting et al (2004) reported increased tolerance in field corn hybrids and increased metabolism of foramsulfuron when the herbicide was applied with the safener, isoxadifen-ethyl.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a differential tolerance of corn genotypes has been recently described toward acetochlor (2-chloro-N-(ethoxymethyl)-N-(2-ethyl-6-methyl-phenyl)acetamide ; Landi et al ., 1990) and to the sulfonylureas DPX-M6316 (3-((((4-methoxy-6-methyl-1,3,5triazin-2-yl)amino)carbonyl)amino) sulfonyl)2thiophene carboxyl acid ; Eberlein et al ., 1989), chlorsulfuron (2-chloroN-(((4-methoxy-6methyl-1,3,5triazin-2-yl)amino)carbonyl) -benzene sulfonamide : Landi et al ., 1989) primisulfuron (2-(3-(4,6-bis(difluoromethoxy)pyrimidin-2-yl)ureidosulfonyl) benzoic acid methyl ester ; Harms et al ., 1990), and nicosulfuron (2-(((((4,6-dimethoxy-2-pyrimidinyl) amino)carbonyl)amino)sulfonyl) N,Ndimethyl-3-pyridine carboxamide ; Stall & Bewick, 1992) . On the other hand, a differential response to glyphosate has been reported among weeds (Duncan & Weller, 1987) .…”
Section: Introductionmentioning
confidence: 99%